PENGARUH SERVIS QUALITY DAN LOKASI TERHADAP KEPUASAN KONSUMEN PADA RUMAH MAKAN PONDOK MAKAN MW KECAMATAN TUGUMULYO LUBUK LINGGAU - Nugroho, Bayu; Islamuddin, Islamuddin (UM. Bengkulu, 2024)
The research was conducted at MW Restaurant in Tugu Mulyo Subdistrict, Lubuk Linggau, with the research problem formulation: How is the Influence of Services Quality and Location on Customer Satisfaction at MW Restaurant in Tugu Mulyo Subdistrict, Lubuk Linggau? The population used in this study was all customers at respondents. The sampling techniques used total sampling based on predetermined criteria, with a total of 150 respondents. Data collection techniques included observation, documentation and questionnaires. The data, once processed, were analyzed using SPSS 24 formulas. Based on the results of the research conducted on the Influence of Services Quality has a significant effect on Customer Satisfaction at MW Restaurant in Tugu Mulyo Subdistrict, Lubuk Linggau. This is evidenced by the t – test results showing values > (6.388 > 1.989) and (sig = 0,000 < 0,050). This means it is rejected and accepted. Location also has a significant effect on Customer Satisfaction at MW Restaurant in Tugu Mulyo Subdistrict, Lubuk Linggau. This is evidenced by the t – test results showing values > (2.806 > 1.989) and (sig = 0,006 < 0.050). This means it is rejected and accepted. Services Quality 0 and Location 0 together have a significant effect on Customer Satisfaction (Y) at MW Restaurant in Tugu Mulyo Subdistrict, Lubuk Linggau. This is evindeced by the F – test showing values > (28.753 > 3.950) and (sig = 0,000 < 0.050). this mean it is rejected and accepted. Based on the correlation coefficient test, the obtained value of R = 0.641 and the determination coefficient = 0.411 have meaning that Service Quality (X1) and Location (X2) contribute an Influence of 0.411 or 47.6% on Customer Satisfaction (Y) at MW Restaurant in Tugu Mulyo Subdistrict, Lubuk Linggau, while the remaining -.589 or 58.9% is influenced by other variables not influenced in this study Keywords: Quality Service, Location, Customer Satisfaction